STARTER-GENERATOR SYSTEM FOR AUXILIARY POWER UNIT - A. V. Levin; S. P. Khalyutin; A. O. Davidov; B. V. Zhmurov; S. A. Kharitonov; M. A. Zharkov; A. S. Kharitonov (Научный вестник МГТУ ГА)
The article presents a starter-generator system for an auxiliary power unit of an aircraft. A feature of the presented system is the use of a synchronous generator with excitation from permanent magnets and a semiconductor converter. The main problem of the system is the generation of electric energy of an aircraft on the basis of a synchronous generator with excitation from permanent magnets is the absence of the possibility of regulating the voltage and frequency of electrical energy, in this connection, a semiconductor converter that ensures the conversion of generated electric energy with significant mass-dimensions characteristics.The article proposes an approach to designing a starter-generator system with a parallel connection of a synchronous generator with excitation from permanent magnets and a semiconductor converter. This approach makes it possible to significantly reduce the part of the electrical energy that needs to be converted, as a consequence, the semiconductor converter has significantly smaller mass-and-batch characteristics.In the article the modes of generation of electric energy and the starter mode of operation of the starter-generator system are considered in detail, the circuit realization of the semiconductor converter is shown. A scheme for replacing one phase of the system for generating electric energy and calculating electric parameters is presented.The possibility of creating a highly efficient starter-generator system based on a synchronous generator with excitation from permanent magnets and a semiconductor converter for an auxiliary power plant of aircrafts is shown. Structural and basic schemes for constructing a system for generating electrical energy are proposed. The approach to the choice of rational circuit solutions is substantiated, basic estimates of the electrical parameters of the system are obtained. The possibility of achieving a specific mass of a semiconductor converter for synchronous generators of 0.21÷0.33 kg/kW is shown.